Neurogenic pain relief by repetitive transcranial magnetic cortical stimulation depends on the origin and the site of pain. Issue 4 (16th March 2004) - Lefaucheur, J-P; Drouot, X; Menard-Lefaucheur, I; Zerah, F; Bendib, B; Cesaro, P; Keravel, Y; Nguyen, J-P
Abstract : Objective: Drug resistant neurogenic pain can be relieved by repetitive transcranial magnetic stimulation (rTMS) of the motor cortex. This study was designed to assess the influence of pain origin, pain site, and sensory loss on rTMS efficacy. Patients and methods: Sixty right handed patients were included, suffering from intractable pain secondary to one of the following types of lesion: thalamic stroke, brainstem stroke, spinal cord lesion, brachial plexus lesion, or trigeminal nerve lesion. The pain predominated unilaterally in the face, the upper limb, or the lower limb. The thermal sensory thresholds were measured within the painful zone and were found to be highly or moderately elevated. Finally, the pain level was scored on a visual analogue scale before and after a 20 minute session of "real" or "sham" 10 Hz rTMS over the side of the motor cortex corresponding to the hand on the painful side, even if the pain was not experienced in the hand itself. Results and discussion: The percentage pain reduction was significantly greater following real than sham rTMS (−22.9% v −7.8%, p = 0.0002), confirming that motor cortex rTMS was able to induce antalgic effects. These effects were significantly influenced by the origin and the site of pain. For pain origin, results were worse in patients with brainstem stroke, whatever the site of pain. This was consistent with a descending modulation within the brainstem, triggered by the motor corticothalamic output. For pain site, better results were obtained for facial pain, although stimulation was targeted on the hand cortical area. Thus, in contrast to implanted stimulation, the target for rTMS procedure in pain control may not be the area corresponding to the painful zone but an adjacent one. Across representation plasticity of cortical areas resulting from deafferentation could explain this discrepancy. Finally, the degree of sensory loss did not interfere with pain origin or pain site regarding rTMS effects. Conclusion: Motor cortex rTMS was found to result in a significant but transient relief of chronic pain, influenced by pain origin and pain site. These parameters should be taken into account in any further study of rTMS application in chronic pain control.